Evolution of eolian relief of the Kaamasjoki–Kiellajoki river basin in Finnish Lapland - Matti Seppälä (Fennia: International Journal of Geography, 1971)
The aim of this study is to explain the dunes and deflation relief formed from sediments accumulated in an ice‑dammed lake during the deglaciation in the Kaamasjoki‑Kiellajoki river basin (69°15’‑69°25'N, 26°30'‑27°05'E). At present the dunes are parabolic fossil dunes formed in periglacial conditions having been deposited by winds blowing from directions lying between WNW and NW. In the subarctic conditions prevailing today eolian activity resulting from the fact that effective wind directions are between W and SW is principally one of deflation.